The Implementation of Duolingo Application to Enhance English Learning for Millennials - Nita, Sekreningsih; Sari, Eka Resty Novieta; Sussolaikah, Kelik; Risky, Satrio Muhammad Fathur (Journal International of Lingua and Technology, 2023)
With the rapid development of information technology, millennials prefer learning english instantly digitally by using an internet connection that can be accessed anyone, anytime and anywhere. The Duolingo application is one of those modern application that facilitate language acquisition by offering an english course model based on everyday life in a simple way. This research used qualitative method with 30 millennial participants and data collection was carried out by giving questionnaires and direct interviews. The results of the study stated learning english with duolingo that 46,67% can given many opportunites for users society, 56,67 % to learn independently and 36,67% can learn outside of the classroom. Positive impact on millennials become more motivated and practice more often and are skilled in applying it in everyday life. Besides that, the mastery of vocabulary becomes more, it is easy to memorize grammar and pronunciation because this application provides acombination of abilities in pronouncing and translating words from pictures. So Duolingo App is a fun combination of text elements with audio-visual questions. With the gamification system offered by Duolingo app, it can help build interest in learning in a way that is comfortable and doesn't get bored easily when studying, especially by millennials.